A randomized, multicenter phase II study comparing efficacy, safety and tolerability of two dosing regimens of cisplatin and pemetrexed in patients with advanced or metastatic non-small-cell lung cancer. (March 2021) - Metzenmacher, Martin; Kopp, Hans-Georg; Griesinger, Frank; Reinmuth, Niels; Sebastian, Martin; Serke, Monika; Waller, Cornelius Florian; Thomas, Michael; Eggert, Jochen; Schmid-Bindert, Gerald; Hoiczyk, Mathias; Christoph, Daniel Christian; et al.
Background: Pemetrexed and cisplatin is a first-line standard in non-squamous non-small-cell lung cancer without targetable mutations. It became the backbone of checkpoint-inhibitor–chemotherapy combinations. Single high doses of cisplatin pose toxicity risks and require hyperhydration, potentially prolonging outpatient application. The aim of this study was to compare efficacy, safety and tolerability of split-dose cisplatin with the standard schedule. Methods: Patients with metastatic non-squamous non-small-cell lung cancer were randomly assigned to up to six 21-day cycles of pemetrexed 500 mg/m 2 and cisplatin 75 mg/m 2 on day 1 (arm A), or pemetrexed 500 mg/m 2 (day 1) and cisplatin 40 mg/m 2 (day 1 + 8, arm B), followed by pemetrexed maintenance. Primary endpoint was objective response rate. Secondary objectives were overall survival, progression-free survival, time to progression, treatment compliance, toxicity profile, and quality of life. Results: We enrolled 130 patients (129 evaluable). Median cycle numbers in A and B were six (1–6) and five (1–6). Dose intensities were comparable between arms. More patients in A received pemetrexed maintenance (24.2% versus 11.1%). With 16 (24.2%) in A and 19 (30.2%) patients in B achieving objective responses [odds ratio 0.74 (0.34–1.62), p  = 0.55] the primary endpoint was met. Overall survival was not different between arms (median 14.4 versus 14.9 months); [HR = 1.07; (0.68–1.68), p  = 0.78]. Median progression-free survival was 7.0 months in A and 6.2 months in B [HR = 1.63; (1.17–2.38); p  = 0.01]. Adverse events of CTCAE grade ⩾3, particularly hematological, were more frequent in B. No difference in grade 4 and 5 infections between arms was noted. Treatment-related asthenia and nausea/vomiting of any grade were more frequent in A. Global health status, fatigue and constipation measured on day 1 of cycle 4 demonstrated superior scores in B. Conclusion: Pemetrexed and split-dose cisplatin is safe and effective. Advantages of split-dose cisplatin with regard to specific toxicities allow personalization of this important chemotherapy backbone. Trial Registration: European Clinical Trials Database (EudraCT) number 2011-001963-37.